Eco-correlation in acidification scenarios - Ove Wolfgang (University of Oslo, Department of Economics, 2001)
The bulk of acid depositions, which have harmful effects on the environment, are caused by foreign emissions in many European countries. Therefore, if some countries emit more acids, one cannot be sure that countries that emit less will benefit from reduced acid depositions. However, numerical simulations with the RAINS model indicate that differences in costs and acid depositions are negatively correlated when equally expensive cost-effective scenarios for Europe are compared, and scenarios only differ with respect to the constraints on depositions at various locations. The negative correlation is twofold: both the signs of changes for individual countries and the magnitude of changes between countries are negatively correlated. The novelty of this paper is to explain these findings. It is shown how the structure of atmospheric transport coefficients must be accounted for in order to understand the numerical findings. Since the atmospheric transport coefficients are constant, the hypothesis is that the two types of correlation will exist for all targets on acidification in Europe. This insight can help policymakers to agree upon a methodology for calculating targets for acidification, and maybe it also can help them to find a consensus upon more ambitious policies towards acidification.
Keywords: D62; H77; Q25; Q28; 330; Acidification; Abatement costs; Environmental constraints; RAINS model; Transboundary air pollution; Saurer Regen; Schwefelsäure; Luftreinhaltung; Umweltschutzkosten; Theorie